2006
DOI: 10.1385/ir:36:1:147
|View full text |Cite
|
Sign up to set email alerts
|

Immune Regulation by the TIM Gene Family

Abstract: Recent studies have demonstrated that proteins of the T cell immunoglobulin and mucin domain (TIM) family are important regulators of immune function. Here we discuss the functional effects of TIM proteins on immune responses, how the effects of TIM proteins may be modulated by interactions with ligands and the limited information available on intracellular signals downstream of TIM proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…We do not believe that our results can be attributed merely to overexpression in a particular cell line. First, our previous studies of the Tim family proteins Tim-1 and Tim-2 with this system have yielded results largely consistent with those obtained with other approaches (12,14,19,30). Also, although many of our reporter activation studies were initially carried out with the Jurkat human leukemic line, we have validated our findings with a nontransformed murine T-cell clone (D10) that, like Jurkat, does not express endogenous Tim-3.…”
Section: Discussionsupporting
confidence: 85%
“…We do not believe that our results can be attributed merely to overexpression in a particular cell line. First, our previous studies of the Tim family proteins Tim-1 and Tim-2 with this system have yielded results largely consistent with those obtained with other approaches (12,14,19,30). Also, although many of our reporter activation studies were initially carried out with the Jurkat human leukemic line, we have validated our findings with a nontransformed murine T-cell clone (D10) that, like Jurkat, does not express endogenous Tim-3.…”
Section: Discussionsupporting
confidence: 85%
“…Since some ISR have only a modest phenotype when the gene is deleted in mice (e.g. Tim3 [67]), any undesirable consequences of blockade will similarly depend on the specific ISR targeted.…”
Section: Inhibitory Signaling Receptor Expression In Til Mediates Dysmentioning
confidence: 99%
“…Of these family members, TIM-1 has been implicated in the immune regulation of asthma and atopic diseases (3,4). More recent studies have shown that ligation of TIM-1 with an agonistic Ab or with a ligand (TIM-4) can costimulate proliferation of T cells as well as cytokine production, both in vivo and in vitro, and abrogate tolerance in a Th2 model of respiratory tolerance, collectively suggesting that it usually functions as a positive immune regulator (5,6).…”
Section: P Roteins Of the T Cell Ig And Mucin Domain (Tim) 3 Familymentioning
confidence: 99%